2021
DOI: 10.3390/microbiolres12040059
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolite Production and Terpenoid Biosynthesis in Endophytic Fungi Cladosporium cladosporioides Isolated from Wild Cymbopogon martinii (Roxb.) Wats

Abstract: Endophytic fungi Cladosporium cladosporioides (F1-MH810309) and Cladosporium tenuissimum (F2-MN715834) from the leaf of wild Cymbopogon martinii (MT90507) were isolated and selected based on the persistent occurrence during different seasons of the year. They were identified based on the morphological features and molecular characterization (ITS sequence), and later deposited at NCBI. Phytochemical studies on F1, F2 and host extracts showed the presence of alkaloids, flavonoids, phenols, terpenoids and tannins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Specifically, 2,4-di-tert-butylphenol is one of the abundant compounds produced by L. theobromae, and its UV-treated mutants, and has been recorded to have several biological activities (Nwobodo et al, 2022). This finding is in agreement with the report of Jayaram et al (2021), that 2,4-di-tert-butylphenol is a major compound produced by different endophytes with several therapeutic applications.…”
Section: Identification Of Bioactive Compoundssupporting
confidence: 94%
See 1 more Smart Citation
“…Specifically, 2,4-di-tert-butylphenol is one of the abundant compounds produced by L. theobromae, and its UV-treated mutants, and has been recorded to have several biological activities (Nwobodo et al, 2022). This finding is in agreement with the report of Jayaram et al (2021), that 2,4-di-tert-butylphenol is a major compound produced by different endophytes with several therapeutic applications.…”
Section: Identification Of Bioactive Compoundssupporting
confidence: 94%
“…Peak area is directly proportional to the concentration of the compound present in the solvent. Most of the listed compounds detected from the fungal endophytes in this study have been produced by other species of endophytic fungi in other studies, and observed to have varying biological properties (Guimarães et al, 2019;Jayaram et al, 2021;Khaled et al, 2021). The bulk of the active compounds identified by GC-MS in this study are essential oils, which may contribute to the antibacterial activity shown against pathogenic bacteria that are susceptible to them.…”
Section: Identification Of Bioactive Compoundsmentioning
confidence: 67%
“…1 lter paper and the resulting ltrate was extracted with ethyl acetate as the solvent system (1:1). The extract was concentrated under decreased pressure and evaporated to dryness at 40°C using a rotating vacuum evaporator (Jayaram et al 2021).…”
Section: Extraction and Gas-chromatography -Mass Spectroscopy Analysi...mentioning
confidence: 99%